Evolution of forced shear flows in polytropic atmospheres: a comparison of forcing methods and energetics. Issue 1 (3rd August 2016) - Witzke, V.; Silvers, L. J.; Favier, B.
Abstract : Shear flows are ubiquitous in astrophysical objects including planetary and stellar interiors, where their dynamics can have significant impact on thermochemical processes. Investigating the complex dynamics of shear flows requires numerical calculations that provide a long-time evolution of the system. To achieve a sufficiently long lifetime in a local numerical model, the system has to be forced externally. However, at present, there exist several different forcing methods to sustain large-scale shear flows in local models. In this paper, we examine and compare various methods used in the literature in order to resolve their respective applicability and limitations. These techniques are compared during the exponential growth phase of a shear flow instability, such as the Kelvin–Helmholtz (KH) instability, and some are examined during the subsequent non-linear evolution. A linear stability analysis provides reference for the growth rate of the most unstable modes in the system and a detailed analysis of the energetics provides a comprehensive understanding of the energy exchange during the system's evolution. Finally, we discuss the pros and cons of each forcing method and their relation with natural mechanisms generating shear flows.